2019
DOI: 10.1080/10962247.2019.1596993
|View full text |Cite
|
Sign up to set email alerts
|

A factor analysis of residents’ performance in municipal solid waste source-separated collection: A case study of pilot cities in China

Abstract: To explore the potential effectiveness of a localized waste recycling system in Chinese cities, several rounds of a municipal solid waste source-separated collection (MSWSC) program were implemented throughout China from 2000 to 2017. In our study, to evaluate the achievements of the MSWSC program, a structured questionnaire survey and face-to-face interviews were conducted in eight representative cities from the MSWSC pilot cities. Influencing factors were examined via a Hierarchical Linear Model (HLM) on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Many studies focus on residents' satisfaction with SWMS from local government in rural or urban regions before a mandatory or demonstration policy, but there is a lack of evaluations about the satisfaction with national policy or services and the central-local and urban-rural comparison [43][44][45][46][47][48][49][50][51][52]. In China, many studies have analyzed rural residents' satisfaction in specific regions-for example, Jiangsu, Beijing, Hunan and Hangzhou Province-and showed that the level of satisfaction is 77%, 67%, 65% and 58%, respectively [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies focus on residents' satisfaction with SWMS from local government in rural or urban regions before a mandatory or demonstration policy, but there is a lack of evaluations about the satisfaction with national policy or services and the central-local and urban-rural comparison [43][44][45][46][47][48][49][50][51][52]. In China, many studies have analyzed rural residents' satisfaction in specific regions-for example, Jiangsu, Beijing, Hunan and Hangzhou Province-and showed that the level of satisfaction is 77%, 67%, 65% and 58%, respectively [43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have analyzed satisfaction with SWMS using national data; for example, Li et al showed that 85% of households were satisfied with waste collection facilities provided by local government using the data from 1450 households of seven provinces in rural China [47]. Other research works showed urban residents' satisfaction with municipal solid waste management services-for example, the detailed non-pilot city of Tongling, some pilot cities of Harbin and Xining and all pilot cities-and found that 34%, 44%, 17% and 20% residents were satisfied with SWMS, respectively [48][49][50][51]. There are a few studies that have analyzed satisfaction with SWMS using nationwide data; for example, Wang et al showed that 65% of residents were satisfied with waste separation bins using data from 672 respondents of 31 provinces in urban China [38].…”
Section: Introductionmentioning
confidence: 99%
“…The NCs and PMCs are responsible for HSW sorting in the model. Thus, we focus on two aspects: (i) the constraints of laws and regulations, including levying financial penalties for not sorting and rewarding points for participation (Zou et al, 2019); and (ii) the promotion of publicity and education. Specifically, the responsible parties should actively promote sorting to create an atmosphere where all residents participate.…”
Section: Subjective Normsmentioning
confidence: 99%
“…Although residents in Jinan have begun to pay attention to waste classification, many problems hinder them from engaging in waste sorting, including a long-term lack of relevant education and a sound waste classification system. These problems are prevalent in other waste classification pilot cities (Zou et al 2019). Therefore, a more nuanced understanding of barriers and dilemmas to sorting waste in China is warranted and Jinan city offers an important case to investigate the affecting factors of community residents engaged in waste classification.…”
Section: Introductionmentioning
confidence: 99%